Molecular MRI of atherosclerosis - Phinikaridou, Alkystis; Andia, Marcelo E.; Lacerda, Sara; Lorrio, Silvia; Makowski, Marcus R.; Botnar, Rene M. (Molecules, 2013)
Despite advances in prevention, risk assessment and treatment, coronary artery disease (CAD) remains the leading cause of morbidity and mortality in Western countries. The lion's share is due to acute coronary syndromes (ACS), which are predominantly triggered by plaque rupture or erosion and subsequent coronary thrombosis. As the majority of vulnerable plaques does not cause a significant stenosis, due to expansive remodeling, and are rather defined by their composition and biological activity, detection of vulnerable plaques with x-ray angiography has shown little success. Non-invasive vulnerable plaque detection by identifying biological features that have been associated with plaque progression, destabilization and rupture may therefore be more appropriate and may allow earlier detection, more aggressive treatment and monitoring of treatment response. MR molecular imaging with target specific molecular probes has shown great promise for the noninvasive in vivo visualization of biological processes at the molecular and cellular level in animals and humans. Compared to other imaging modalities; MRI can provide excellent spatial resolution; high soft tissue contrast and has the ability to simultaneously image anatomy; function as well as biological tissue composition and activity. © 2013 by the authors.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Contrast agent; Molecular imaging; MRI